Corrigenda "Samir Amin (1931-2018) y el desarrollo desigual" - Rafael Domínguez-Martín (Revista Iberoamericana de Estudios de Desarrollo)
Corrigenda in the article "Samir Amin (1931-2018) y el desarrollo desigual", published in the Volume 8, issue 2.